1990
DOI: 10.1099/00221287-136-5-965
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of immunosuppressive macrophages induced in spleen cells by Mycobacterium avium complex infections in mice

Abstract: ~_ _ _The profile of generation and characteristics of splenic macrophages (MOs) which suppress the concanavalin A (Con A) mitogenic response of splenic T cells (designated as 'immunosuppressive MOs') in host CBA/JN mice during the course of Mycobacferium avium complex (MAC) infection were investigated. In MAC-infected mice, reductions in some cellular functions of host splenic T cells, such as the Con A mitogenic response and mixed leucocyte reaction, were seen around 2 weeks after challenge of organisms, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…This inhibitory activity was partly attributable to a hydrophobic substance which contained phosphatidylglycerol. Previously we found that the suppressor activity of MAIC-induced macrophages was abrogated by cytochalasin B [5], thereby indicating the essential role of membrane function of these macrophages in the expression of their immunosuppressive activity. This suggests that cell-to-cell interaction is also important in the case of MAICinduced macrophages.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This inhibitory activity was partly attributable to a hydrophobic substance which contained phosphatidylglycerol. Previously we found that the suppressor activity of MAIC-induced macrophages was abrogated by cytochalasin B [5], thereby indicating the essential role of membrane function of these macrophages in the expression of their immunosuppressive activity. This suggests that cell-to-cell interaction is also important in the case of MAICinduced macrophages.…”
Section: Discussionmentioning
confidence: 88%
“…Con A-induced mitogenesis of SPC was measured as reported previously [5]. Briefly, 2 : 5 2 10 5 SPC were cultured in 0 .…”
Section: Mitogenic Response Of Spcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of pathogens, DCs maintain T cell unresponsiveness by presenting self-Ags without costimulation (2). In addition, M⌽ suppress T cell activity (3). In contrast, pathogen ligation of TLRs activates DCs and M⌽ by inducing costimulatory molecules and promoting cytokine secretion.…”
mentioning
confidence: 99%
“…Dendritic cells (DCs) 3 and macrophages (M⌽) regulate the balance between immunity and tolerance by controlling lymphocyte activation. In the absence of pathogens, DCs maintain T cell unresponsiveness by presenting self-Ags without costimulation (2).…”
mentioning
confidence: 99%